2008
DOI: 10.1002/cphc.200700720
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Dissociation of Anions Formed by Electron Attachment

Abstract: A comprehensive analysis of metastable dissociation of 2,4-dinitrotoluene (DNT) parent anions formed by attachment of electrons of controlled energy is presented. We characterize the energy dependence and kinetic energy release of the reaction which competes with autodetachment. A surprising finding is a highly exothermic metastable reaction triggered by the attachment of thermal electrons which we relate to the well-known electrostatic ignition hazards of DNT and other explosives. Quantum chemical calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
(26 reference statements)
2
17
0
Order By: Relevance
“…A remarkable exception is electron attachment to C 60 (and other fullerenes) generating metastable parent anions up to electron energies of 10 eV [32]. We again note that very recent experiments on di-nitrotoluene [20] revealed that low energy electron attachment leads to both prompt DEA and a metastable decomposition of the transient anion.…”
Section: Parent Molecular Anion (Associative Attachment) M − /C 6 H 4mentioning
confidence: 85%
See 1 more Smart Citation
“…A remarkable exception is electron attachment to C 60 (and other fullerenes) generating metastable parent anions up to electron energies of 10 eV [32]. We again note that very recent experiments on di-nitrotoluene [20] revealed that low energy electron attachment leads to both prompt DEA and a metastable decomposition of the transient anion.…”
Section: Parent Molecular Anion (Associative Attachment) M − /C 6 H 4mentioning
confidence: 85%
“…It was recently demonstrated [18] by measuring the NO 2 − resonance energies for a series of nitro aromatic compounds including isomers that it is possible to distinguish between the different compounds. DNT has recently been studied by the combined use of a time-of-flight mass spectrometer and two sector field magnetic mass spectrometer [20]. It is found that the transient negative ion formed upon electron attachment promptly decomposes by the loss of neutral H 2 O, N 2 O and further fragments.…”
Section: Introductionmentioning
confidence: 99%
“…22) lending evidence to their more explosive character when compared to other explosives such as TNT 20 and the other nitrocompounds. [16][17][18][19]23,24,26 In Figure 3 we show the fully optimized geometry obtained at MP2/6-311++G(2d,p)…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…This value is even larger than the KER found for metastable loss of NO from 2,4-dinitrotoluene after lowenergy electron attachment, which was 0.7 eV. 9 The MIKE peak in Fig. 8(c) corresponds to a much narrower MaxwellBoltzmann-type KER distribution; the average KER is only 0.13 eV.…”
Section: Metastable Peak Shapes and Kinetic Energy Releasementioning
confidence: 78%
“…[6][7][8] Some of the fragments of DNB anions feature larger electron affinities which, combined with the low thermochemical stability of neutral DNB, implies that attachment of lowenergy electrons to DNB may trigger dissociative reactions that are accompanied by large kinetic energy release (KER), similar to a recently described highly exothermic reaction for electron attachment to 2,4-dinitrotoluene. 9 Interestingly, these reactions may occur in the metastable time window, i.e., microseconds after electron attachment. Bowie et al 10 have reported kinetic energy release values of 0.5-1.0 eV for the metastable reaction DNB + e → DNB * − → (DNB-NO) − + NO,…”
Section: Introductionmentioning
confidence: 99%